On Gibbs quantum and classical particle systems with three-body forces - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
For equilibrium quantum and classical systems of particles interacting via ternary and pair (nonpositive) infinite-range potentials, a low activity convergent cluster expansion for their grand canonical reduced density matrices and correlation functions is constructed in the thermodynamic limit.